Prenatal diagnosis of i(18q) and dup(18q) cases by quantitative fluorescent PCR - Castro Volio, Isabel (2013)
Particular sonographic fetal malformations are common in chromosome 18 aberrations, requiring invasive prenatal tests to confirm the diagnosis. Karyotyping is the gold standard assay in these cases, although it is a high complexity, expensive and approximately 2 weeks turnaround time test. On the contrary, quantitative fluorescent PCR is considered an accurate, simple, low cost and rapid assay, particularly useful for the diagnosis of aneuploidies of chromosomes 13, 18 and 21 and for the detection of maternal cell contamination of the sample. Clinical presentation of two cases of rare chromosome 18 defects, diagnosed using both techniques. One case was an isochromosome and the other was a partial duplication. Quantitative fluorescent PCR was an invaluable tool for the cytogenetics laboratory.